A methods engineering study on Pier Angelo Handicrafts - Cabardo, Laser A.; Ong, Gerry; Santeco, Ryan.; Segovia, Cesar (Diliman, Quezon City College of Engineering, 1999)
This study was made on Pier Angelo Handicraft Enterprise in view of the need to develop an efficient system of operations in the plant and to simplify procedures. Through the utilization of the techniques of Work Study, the present ways of doing work in the plant were systematically analyzed and critically examined. The group observed three major problems in the plant. These are : poor work station design, no systems and procedures, poor ventilation. Proposals in the following key areas were developed to increase the efficiency of operations : 1. plant layout- optimize loom dimension to save on floor space. 2. working conditions and environment - redesign loom; improve ventilation, introduce backrests on seats for workers; provide two fire extinguishers. 3. Systems and Procedures - documentation and creation of necessary forms. Upon implementation of these recommendations, it is expected that : worker productivity will be increased by at least 2.11 percent per roll of raw material, worker health and safety will be improved, there will be a proper systems and procedures, floor space will be saved by 47,712 square inches.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis